2017
DOI: 10.1186/s12889-017-4520-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthy dietary patterns decrease the risk of colorectal cancer in the Mecca Region, Saudi Arabia: a case-control study

Abstract: BackgroundColorectal cancer (CRC) is the first most common cancer in males and the third most common cancer in females in Saudi Arabia. Dietary habits are strongly associated with the inhibition or proliferation of malignancy. Therefore, this study is aiming to investigate the risks and protective benefits of dietary factors affecting CRC in the Mecca region of Saudi Arabia.MethodsA case-control study was conducted from June 2014 to March 2015. One hundred thirty-seven patients with colon and/or rectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
5
23
0
4
Order By: Relevance
“…To our knowledge, this study is the first study to examine the association between diet and lifestyle indices, and CRC among the Omani population. In our study, the dietary pattern of CRC cases had a statistically significant trend towards low vegetables and fruits intake which is similar to the finding by other authors from Saudi Arabia (Alamri et al, 2014;Azzeh et al, 2017). These authors examined the dietary habits of CRC cases and matched controls among a sample of Saudi participants and found that participants in the control group consumed more fruits and vegetables than the CRC cases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this study is the first study to examine the association between diet and lifestyle indices, and CRC among the Omani population. In our study, the dietary pattern of CRC cases had a statistically significant trend towards low vegetables and fruits intake which is similar to the finding by other authors from Saudi Arabia (Alamri et al, 2014;Azzeh et al, 2017). These authors examined the dietary habits of CRC cases and matched controls among a sample of Saudi participants and found that participants in the control group consumed more fruits and vegetables than the CRC cases.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies on Western populations have looked into the association between diet and lifestyle factors and CRC (Levi et al, 2002;Boyle et al, 2013;Johnson et al, 2013;Baroudi et al, 2014). Of the few such studies conducted in the Arab countries of the Middle East (Arafa et al, 2011;Alamri et al, 2014;Azzeh et al, 2017), none has examined the association between dietary and lifestyle indices and CRC in the Omani population despite the documented rise in CRC incidence in Oman over the past decade. Therefore, the overall aim of this study was to examine the association between dietary and lifestyle indices, and CRC among Omani cases and controls attending a tertiary hospital in Oman.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies that reported positive association between intake of leafy green vegetables and decrease risk of CRC (Tantamango et al 2011;Azzeh et al 2017) , in our study patients in the CRC group had lower intakes compared with controls (p<0.001). One possible mechanism explaining the protective properties of leafy green vegetables might be associated with their chlorophyll content which can modify genotoxic effects of known toxins (Tantamango et al, 2011).…”
Section: Dietary Intakesupporting
confidence: 92%
“…As showed in Figure 3(b) patients with CRC consumed less daily intake of these foods compared to the control group. To prevent CRC, WHO recommends a daily intake of at least 400 grams of non-starchy fruits and vegetables, emphasizing the risk associated with insufficient intake, as found in our research and corroborated by other similar studies [8] [53].…”
Section: Dietary Variablessupporting
confidence: 90%